Human brown adipose tissue assessed by simple, noninvasive near‐Infrared time‐resolved spectroscopy. (10th April 2015) - Nirengi, Shinsuke; Yoneshiro, Takeshi; Sugie, Hiroki; Saito, Masayuki; Hamaoka, Takafumi
<x xml:space="preserve">Abstract</x> Objective Human brown adipose tissue (BAT) activity has been typically evaluated by 18F‐fluorodeoxyglucose (FDG)‐positron emission tomography (PET) combined with computed tomography (CT). However, FDG‐PET/CT has serious limitations (e.g., radiation and cold exposure). This study evaluated BAT density using near‐infrared time‐resolved spectroscopy (NIRTRS), a simple and noninvasive method of measuring the indices of tissue hemoglobin concentration [total‐Hb] and mitochondrial density (µs′). Methods The NIRTRS parameters at 760, 800, and 830 nm in the supraclavicular region potentially containing BAT were evaluated. First, the NIRTRS parameters were compared at 27°C and during a 2‐h cold exposure (19°C) in 18 men. Then, NIRTRS parameters at 27°C were compared with mean standardized uptake values (SUVmean) assessed by FDG‐PET/CT after the 2‐h cold exposure (19°C) in 29 men. Results There was no significant difference between the NIRTRS parameters at 27°C and 19°C. The [total‐Hb] and µs′ were significantly correlated to SUVmean (r = 0.73 and r = 0.64, respectively). A receiver operating characteristic analysis revealed that the sensitivity (75.0‐82.4%), specificity (91.7‐100%), and accuracy (82.8‐86.2%) of the NIRTRS parameters were all good to determine the NIRTRS reliability. Conclusions Our novel NIRTRS method is noninvasive and simple and can reliably assess human BAT density in the supraclavicular region.